The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1463-5224.2007.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of retinal vessel patterns in ophthalmically normal dogs

Abstract: This methodology may be useful to differentiate between normal and pathologic states of canine retinal vascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
1
Order By: Relevance
“…Family et al (17) calculated the fractal dimension (D) of the vascular pattern of the human retina using mass radius (D = 1.71 ± 0.07) and correlation (D = 1.72 ± 0.03) methods, but did not observe a significant difference between them. Previous studies from our group have shown that the fractal dimension values depend on the method used for the calculation of the fractal structure (27,28). In the present study, we showed that box-counting and information fractal dimensions differ significantly in each region as well as in the whole retina.…”
Section: Discussionmentioning
confidence: 99%
“…Family et al (17) calculated the fractal dimension (D) of the vascular pattern of the human retina using mass radius (D = 1.71 ± 0.07) and correlation (D = 1.72 ± 0.03) methods, but did not observe a significant difference between them. Previous studies from our group have shown that the fractal dimension values depend on the method used for the calculation of the fractal structure (27,28). In the present study, we showed that box-counting and information fractal dimensions differ significantly in each region as well as in the whole retina.…”
Section: Discussionmentioning
confidence: 99%
“…Fractal analysis is not new in veterinary medicine. It has been used in horses to examine the microscopic appearance of cancellous bone where findings have compared with measurements of bone strength, such as Young's modulus 23 and in dogs to characterize micro‐fractures 24 and retinal blood vessels, 25 but it has not been used in the assessment of gross images in animals. In the limited application described here fractal analysis contributed little over and above a subjective qualitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For the selected year 2008, the Wiley online “Citing Literature” tool was used to identify the specific journals and textbooks that cited each VO article published that year. For example, the two citations of the first article published in VO in 2008 are listed at the bottom of the respective page on Wiley's website 17 …”
Section: Methodsmentioning
confidence: 99%